2017
DOI: 10.1590/s1678-9946201759032
|View full text |Cite
|
Sign up to set email alerts
|

Presence of rotavirus and free-living amoebae in the water supplies of Karachi, Pakistan

Abstract: Rotavirus and pathogenic free-living amoebae are causative agents of important health problems, especially for developing countries like Pakistan where the population has limited access to clean water supplies. Here, we evaluated the prevalence of rotavirus and free-living amoebae (Acanthamoeba spp., Balamuthia mandrillaris, Naegleria fowleri) in drinking water supplies of Karachi, Pakistan. Six water filtration plants that supply drinking water to the population of Karachi were investigated. Additionally, dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Previous reports have been indicated that Acanthamoeba not internalize poliovirus, vesicular stomatitis virus or echoviruses (Danes and Cerva, 1981;Mattana et al, 2006). Recently, Mimivirus and adenovirus were identified from Acanthamoeba (Scheid and Schwarzenberger, 2012;Yousuf et al, 2017). Because Acanthamoeba and adenovirus or Acanthamoeba and rotavirus, could be detected in the same water sample, we hypothesized that there might be a role for Acanthamoeba in transmission of adenovirus or rotavirus.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous reports have been indicated that Acanthamoeba not internalize poliovirus, vesicular stomatitis virus or echoviruses (Danes and Cerva, 1981;Mattana et al, 2006). Recently, Mimivirus and adenovirus were identified from Acanthamoeba (Scheid and Schwarzenberger, 2012;Yousuf et al, 2017). Because Acanthamoeba and adenovirus or Acanthamoeba and rotavirus, could be detected in the same water sample, we hypothesized that there might be a role for Acanthamoeba in transmission of adenovirus or rotavirus.…”
Section: Discussionmentioning
confidence: 89%
“…Free-living amoebae have been reported to feed by phagocytosis on bacteria, fungi, and algae (Król-Turmińska and Olender, 2017;Chen et al, 2018). According to the previous reports (Scheid and Schwarzenberger, 2012;Yousuf et al, 2017), Acanthamoeba might serve as an environmental reservoir for viruses living in the same environment, such as mimivirus, coxsackievirus and adenovirus. In light of the fact that viruses can become internalized within Acanthamoeba, this is the first study to investigate the transmission of adenovirus and rotavirus via waterborne' Acanthamoeba in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…All of the RoV outbreaks have been associated with direct fecal contamination of untreated, compromised water supply or suboptimal treatment of drinking water. RoV have been detected in surface waters worldwide (Gerba, 1999;Tort et al, 2015;Yousuf et al, 2017). Surface water receiving untreated wastewater effluent; have been reported to contain the highest concentrations of viral pathogens (Griffin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The plates were sealed with parafilm and then incubated at 35 °C for 30 days. Each sample was examined daily by the inverted microscopy to detect trophozoites or cysts of FLA ( Yousuf et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%